The relationship of Islamic performance index and intellectual capital by supply chain management toward banking financial performance in Indonesia - Jummaini Jummaini; Nasir Azis; Faisal Faisal; Hasan Basri; Zikri Muhammad (International Journal of Supply Chain Management, 2019)
This study aims to investigate the relationship between Islamic performance index involving Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Islamic revenues vs Non-Islamic revenues and the efficiency of intellectual capital including physical capital, human capital and structural capital on the financial performance of companies by considering the supply chain management strategy: Return on total assets (ROA).This quantitative study uses a secondary data in the form of annual financial statements. The data are valid because all of them taken from the data published on the websites of each Islamic Commercial Banks and Bank Indonesia website. The population of this study is 12 Islamic Commercial Banks in Indonesia from 2012 to 2016. This study uses multiple linear regression analysis to determine the effect of Islamic performance index and Intellectual Capital on the financial performances of Islamic Commercial Banks in Indonesia from 2012 to 2016.